2021
DOI: 10.14390/jsshp.hrp2020-002
|View full text |Cite
|
Sign up to set email alerts
|

Uterine necrosis following uterine artery embolism due to postpartum hemorrhage: A case report and review

Abstract: Uterine necrosis after uterine artery embolization (UAE) for postpartum hemorrhage (PPH) is relatively rare. A 29-year-old primiparous woman had a diamniotic dichorionic twin pregnancy following frozen blastocyst transfer. She developed preeclampsia at 34 +3 weeks, and cesarean section was performed due to lung edema at 35 +2 weeks. UAE was performed using a gelatin sponge 3 hours after the operation due to PPH; however, the hemorrhage continued, and we performed a second UAE using n-butyl-2-cyanoacrylate. Ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Our patient was of a young age, received prophylactic antibiotics, and remained hemodynamically stable. There have been reports of possible association of uterine necrosis with hypertensive disorders of pregnancy such as pre-eclampsia, especially due to uterine local circulatory failure associated with intravascular volume depletion [ 10 ] [ 11 ]. The patient in this case did not have this particular risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was of a young age, received prophylactic antibiotics, and remained hemodynamically stable. There have been reports of possible association of uterine necrosis with hypertensive disorders of pregnancy such as pre-eclampsia, especially due to uterine local circulatory failure associated with intravascular volume depletion [ 10 ] [ 11 ]. The patient in this case did not have this particular risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The present case developed uterine necrosis after UAE for PPH and required hysterectomy. There is only one case report of uterine necrosis after UAE in a patient with PE by Hirashima et al [ 8 ]. Pleural effusion, proteinuria, and atonic bleeding were observed in our case as well as the case reported by Hirashima et al In addition, our case showed massive ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced MRI showed loss of contrast enhancement in the internal myometrium, leading us to diagnose uterine necrosis. These imaging findings are characteristic for uterine necrosis [ 8 , 12 ]. In the event of fever of unknown origin or other persistent symptoms indicative of uterine necrosis after UAE, observing the state of the endometrium with abdominal ultrasonography is important for diagnosis.…”
Section: Discussionmentioning
confidence: 99%